Hereditary thrombophilia - Dautaj, Astrit; Krasi, Geraldo; Bushati, Vilma; Precone, Vincenza; Gheza, Miriam; Fioretti, Francesco; Sartori, Marianna; Costantini, Alisia; Benedetti, Sabrina; Bertelli, Matteo (Acta Biomedica Atenei Parmensis, 2019)
Thrombophilia is a group of disorders in which blood has an increased tendency to clot. It may be caused by inherited or acquired conditions. Thrombophilia is associated with risk of deep venous thrombosis and/or venous thromboembolism. Factor V Leiden thrombophilia is the most common inherited form of thrombophilia and prothrombin-related thrombophilia is the second most common genetic form of thrombophilia, occurring in about 1.7-3% of the European and US general populations (3). Thrombophilia may have autosomal dominant, autosomal recessive or X-linked inheritance. Genetic testing is useful for confirming diagnosis and for differential diagnosis, recurrence risk evaluation and asymptomatic diagnosis in families with a known mutation.